STATE POLICY ON PROMOTING EXPORTS IN THE DIGITAL ECONOMY (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article examines the role and effectiveness of public policy in stimulating exports in the digital economy, including export mechanisms, electronic platforms, and the impact of government-provided digital services. It also analyzes practical mechanisms for supporting digital exports and suggests future directions.